2014
DOI: 10.4103/0970-9185.130102
|View full text |Cite
|
Sign up to set email alerts
|

Incidental thrombocytosis: Should it concern the anesthesiologist?

Abstract: Preoperative thrombocytosis, often detected incidentally in surgical patients and inadvertently overlooked, has important implications for the anesthesiologists. The primary form is a chronic clonal myeloproliferative disorder usually affecting adults while the secondary type is a benign reactive disease commonly found in children. Serious perioperative hemostatic complications are reported in primary thrombocytosis and hence, a detailed preoperative evaluation and initiation of therapy to lower the platelet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…While the etiology of thrombocytosis was unknown, reactive thrombocytosis is the leading cause of thrombocytosis in the general medical population and usually occurs as a result of an acute phase response to infection or tissue damage. 7 , 21 , 22 Prior studies found that infected patients may present with thrombocytosis even in the absence of other more obvious signs of infection such as an elevated white blood cell count or fever. 23 , 24 In agreement with the literature in other patient populations, 8 - 10 our findings suggest that thrombocytosis may be a clinical indicator of postoperative infection risk in hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the etiology of thrombocytosis was unknown, reactive thrombocytosis is the leading cause of thrombocytosis in the general medical population and usually occurs as a result of an acute phase response to infection or tissue damage. 7 , 21 , 22 Prior studies found that infected patients may present with thrombocytosis even in the absence of other more obvious signs of infection such as an elevated white blood cell count or fever. 23 , 24 In agreement with the literature in other patient populations, 8 - 10 our findings suggest that thrombocytosis may be a clinical indicator of postoperative infection risk in hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ] Therefore, caution during preoperative evaluation and treatment to reduce platelet counts are considered to be essential before surgery. [ 15 18 ] We chose plateletpheresis to quickly decrease the platelet count, since this has been successfully applied in coronary artery bypass grafting. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Elective surgery should be delayed until platelet counts return to normal levels and any cardiovascular risk factors are addressed. Symptomatic ET patients may require cytoreductive therapy to achieve this, while perioperative thromboprophylaxis may be necessary in emergency cases [ 40 ].…”
Section: Reviewmentioning
confidence: 99%